2013
DOI: 10.1007/s12199-013-0361-7
|View full text |Cite
|
Sign up to set email alerts
|

Significant but weak spousal concordance of metabolic syndrome components in Japanese couples

Abstract: Objective This study was initiated to investigate if spousal concordance in metabolic syndrome (MS) components exist in Japan. Methods In all, 756 couples (mean age: 48.9 and 47.3 years for husbands and wives, respectively) were identified. Each subject was classified as an MS, MS reserves (MSRES) or no risk of MS (NonMS) case after Japanese Ministry of Health, Labour and Welfare (JMHLW) criteria. Criteria of the National Cholesterol Education Program and of the Joint Interim Statement were also applied. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
3
6
0
Order By: Relevance
“…We also found the similar associations in children subsample and spouses subsample. These results were consistent with some other research results 16 23–25. Additionally, the results suggested potential associations between the different chronic conditions, for example, hypertension and diabetes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found the similar associations in children subsample and spouses subsample. These results were consistent with some other research results 16 23–25. Additionally, the results suggested potential associations between the different chronic conditions, for example, hypertension and diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to results using all adult household members, positive associations were found in these two subsamples. These findings were consistent with some previous studies 23–25 29 30. The results of analyses in these two special subsamples showed the effects of genetic factors and those of a common living environment without genetic ties on the associations of interest.…”
Section: Discussionsupporting
confidence: 92%
“…Some reported that there was spousal concordance of cancer [33]; depression [34]; mental disorders [35]; physical frailty [36]; and metabolic components, including overweight/obesity [16,17,34], diabetes [18][19][20]34,37], dysglycemia [17,34], and hypertension [12,16,21,22] among couples. However, one Japanese study revealed that spousal concordance in metabolic components was weak and modest [38]. Some studies reported that spouses show concordance in several dietary behaviors, such as drinking [10][11][12], alcohol consumption [12,13], smoking [16,34], fruit or vegetable consumption [14], irregular eating behaviors [34], and eating salty foods [11].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have explored spousal similarities in cardiometabolic risk factors, such as blood pressure (BP) [12][13][14][15][16][17][18], cholesterol level [13][14][15]17,18], triglycerides (TG) level [13,15,17], abnormal glucose tolerance [12,13,[15][16][17][18][19][20], and smoking [14,19]. Further, a 2008 meta-analysis, showed statistically significant positive spousal concordances for the main coronary risk factors, such as hypertension and diabetes [21].…”
Section: Introductionmentioning
confidence: 99%